2003
DOI: 10.1021/jf0209995
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Pesticide Analysis in Wines by Solid-Phase Extraction and Capillary Gas Chromatography−Mass Spectrometric Detection with Selective Ion Monitoring

Abstract: A method was developed to determine pesticides in wines. The pesticides were extracted from the wine using solid-phase extraction on a polymeric cartridge, and the coextractives were removed with an aminopropyl-MgSO(4) cartridge. Analysis was performed using capillary gas chromatography with electron impact mass spectrometric detection in selective ion monitoring mode (GC-MSD/SIM). Three injections are required to analyze all 153 organohalogen, organonitrogen, organophosphate, and organosulfur pesticides and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…Other authors 16 have reported good recovery results in wine samples when calibration standards were prepared with corn oil as an analyte protectant. These facts suggest that the volatility range covered by the mixture of fatty acids gives good analyte protection despite differences in the composition of corn and olive oils.…”
Section: Analyte Protectantsmentioning
confidence: 94%
See 1 more Smart Citation
“…Other authors 16 have reported good recovery results in wine samples when calibration standards were prepared with corn oil as an analyte protectant. These facts suggest that the volatility range covered by the mixture of fatty acids gives good analyte protection despite differences in the composition of corn and olive oils.…”
Section: Analyte Protectantsmentioning
confidence: 94%
“…Several factors have to be considered in selecting the analyte protectants, such as their volatility and hydrogen-bonding ability. Based on previous studies, 2,3-butanediol, L-gulonic acid γ-lactone 11 and corn oil 16 were selected as protectant agents. Olive oil was also included in the study.…”
Section: Analyte Protectantsmentioning
confidence: 99%
“…Oxyfluorfen is amenable to GC separation (Wong et al, 2003), and nitrofen, with a similar structure, should have favorable properties for GC. Shen (Shen et al, 2008) extracted DPhE from vegetables sample with acetonitrile, then the extract was cleaned up by Envi-Carb SPE column connected to Alumina Neutral SPE column, determined by gas chromatographynegative chemical ionization mass spectrometry.…”
Section: Diphenyl Ether Herbicidesmentioning
confidence: 99%
“…Methods of pesticide analyses have been largely driven by the food industry [1][2][3]. In their comprehensive paper of 2000, Filion et al [4] screened fruit and vegetable samples for 251 known pesticides by extracting pulp with solvent before clean-up on solid phase extraction cartridges.…”
Section: Introductionmentioning
confidence: 99%